(untitled) (Jurnal Ecosolum, 2020)
ABSTRACT The implementation of Jeneberang watershed management is a watershed management priority plan that has been determined by the Government. However, there is no common ground and commitment between the government and all stakeholders, so there are still various problems in the upstream Jeneberang watershed. This study aims to determine the management strategy in the upstream area of ​​the Jeneberang River Basin and to analyze the factors that determine the success of the Jeneberang watershed management strategy. This research uses qualitative and quantitative methods with descriptive analysis techniques and SWOT-AHP analysis. The results of this study explain that the Jeneberang watershed is in the critical category and a priority national watershed in handling. So that it requires the handling of all stakeholders to work together. All stakeholders have the same management goal, which is to maintain sustainability, balance the ecosystem, and help community welfare. However, due to lack of coordination between all stakeholders and budget constraints. The results of the SWOT – AHP analysis show that the success factors in managing the Jeneberang watershed are: 1. Requiring commitment of all stakeholders and providing incentives, education, opening jobs, training and assistance to communities who maintain the sustainability of the upstream Jeneberang watershed. 2. Maximizing and prioritizing the management of the Jeneberang watershed so that erosion and flooding does not occur. 3. Land conversion occurs around the Jeneberang watershed so that it requires intensive handling and supervision from all parties who manage the Jeneberang watershed.